2018
DOI: 10.1007/s10620-018-5267-1
|View full text |Cite
|
Sign up to set email alerts
|

3-Aminobenzamide Prevents Concanavalin A-Induced Acute Hepatitis by an Anti-inflammatory and Anti-oxidative Mechanism

Abstract: Our results suggest that 3-AB has a therapeutic effect on concanavalin A-induced liver injury by inhibiting expression of the key pro-inflammatory cytokine TNFα, via PARP-1-independent NFκB suppression and via an NFκB-independent anti-oxidative mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…5C), consistent with the lack of early ROS production in the absence of NDPK-D. It has been suggested that antioxidants can diminish LPS-induced inflammatory gene activation ( 50 52 ). We therefore tested whether mitochondrial ROS induction contributes to the early transcriptional response.…”
Section: Resultssupporting
confidence: 73%
“…5C), consistent with the lack of early ROS production in the absence of NDPK-D. It has been suggested that antioxidants can diminish LPS-induced inflammatory gene activation ( 50 52 ). We therefore tested whether mitochondrial ROS induction contributes to the early transcriptional response.…”
Section: Resultssupporting
confidence: 73%
“…Experimental Animals. Male wild-type (WT) C57BL/6 mice (purchased from Animal Feeding Center of Xi'an Jiaotong University Health Science Center, Xi'an, China) and male mice with TPH1 (critical rate-limiting enzyme for the synthesis of peripheral serotonin) knockout (TPH1−/−, which originated from C57BL/6 mice, kindly presented by Max Planck Institute for Molecular Genetics, Berlin, Germany, and the genotype was tested by PCR) were used (6)(7)(8) weeks old, 20-25 g). As previously described, the lack of peripheral serotonin is the only difference between TPH1 −/− and WT mice [26].…”
Section: Methodsmentioning
confidence: 99%
“…This model is accompanied by massive liver tissue necrosis, extensive inflammatory response, and prominent hepatocyte apoptosis [5]. In addition, remarkable oxidative stress injury, characterized by significant upregulation in contents of oxidative markers and significant downregulation in activities of antioxidative markers, is closely related to inflammation and Con A-mediated hepatocyte damage [5][6][7][8]. As easy operation, low cost, well repeatability, and close to the pathological process of human viral hepatitis, Con A-induced ALI is regarded as the best experimental model for ALI research [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…221). Since these initial findings, multiple studies demonstrated the involvement of PARP activation in inflammatory reactions (for detailed review see in (Refs 222, 223, 224)), as much as the protective effect of PARP inhibition in acute and chronic inflammation (Refs 225, 226, 227, 228, 229, 230, 231, 232, 233, 234, 235, 236, 237, 238, 239, 240, 241, 242, 243, 244, 245). As the majority of cellular PARP activity in mammals is attributed to PARP1, most of the available data in the context of inflammatory regulation focuses on the role of PARP1.…”
Section: Immunomodulatory Roles Of Parp2mentioning
confidence: 99%